Superprodutos para "super-humanos": o tempo como mercadoria na sociedade de consumo contemporânea - Farias, Vanessa Ester Silva (2014)
In a context of rapid technological development, whose promises of benefits/facilities lead to a cult of fetishized consumption as a producer of subjectivities, we question in this paper the paradox between the accelerated development and the growing scarcity of time experienced by individuals, imprisoning him ever more in comprehensive activities. We seek an analysis of psychosocial impact of market logic, expressed in advertising, on the assumption that the commodity fetishism (Marx) manifests itself today twice: not only alienates the social relations of production, but the very subjectivity of the consumer through “super products”. These aggregate “super powers” such as power, high self-esteem and ability to “all-power” and “all-do”, in record time. It is a result of the dissemination of “superhuman” stereotypes, individuals supposedly capable of dealing with the challenges of late modernity, breaking temporal and spatial barriers, via new technologies. Such advertising stereotypes, in turn, are welcomed to the promises of human needs satisfied, instigating the narcissism of individuals (SEVERIANO, 2007). Namely, it sells the idea of “super products” to keep the imagination of narcissistic “superhuman”, naturalizing themselves in this way, the speed of the living and the performance necessary for the accumulation of capital. So, methodologically, this research appears as a theoretical and empirical investigation, theoretical and methodological axis by the Frankfurt School, plus methodological strategies, which include a selection of advertisements. The advertisements collected do appeal to the acceleration of the pace of life through products and services aimed to produce performances “superhuman”. A first collection of advertisements, based on the most prominent content related to the object of study, it was possible to build the following key categories: Omnipotence; Youth and Recognition. The category of Omnipotence refers to advertisements whose promises revolve around the field of nature, expressing power, via products. The category of Youth comes to the uplifting of science as a way to dominate the time and phases of the cycle of life. While in the category of Recognition refers to advertisements that supposedly promote interpersonal relationships and feelings of belonging, recognition, differentiation, friendship, love, etc. In this sense, the final reflections suggest that the time has been valued in the market as a rare object of consumption, aggregate to superprodutos, which causes an apparent objectification of time the weakening of its real sense and its value in use. In addition, individuals have become receptacles of the most varied demands – entered in the key categories – to become "superhuman", generating intense acceleration of the pace of their lives. It also highlights the prominence of category of Omnipotence, leaving clear that contemporary culture has deprived of rightful place own questions of the human condition (such as weakness, imperfection, sadness, finiteness, etc.), for the incorporation of subjectivities.